(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Merger and Acquisition is the most effective ways to accelerate the growth implementation plan of companies. All industries have been using M&A as an aggressive strategy for growth. Merger and acquisition in is not a new concept and burst in M&A has given further space to companies to look for integration for their growth, market coverage or any other strategic requirement. In today’s globalized economy, competitiveness and competitive advantages have become the buzzwords, for corporate around the world. Corporate restructuring has gained considerable importance all over the world because of intense competition, globalization and technological changes and in this context mergers and acquisitions (M&A) are being increasingly used the world over, for improving competitiveness of companies through gaining greater market share, broadening the portfolio to reduce business risk, for entering new markets and geographies, and capitalizing on economies of scale etc. Mergers are important corporate strategy actions that, among other things, aid the firm in external growth and provide it competitive advantage. This area has spawned a vast amount of literature over the past half a century, especially in the developed economies of the world. India too has been seeing a growth in the number of mergers over the past one-and-a-half decades since economic liberalization and financial reforms were introduced in 1991.